Ethnic Factor in Afghanistan - Muhammad Saleem Mazhar♣ Samee Ozair Khan Naheed S. Goraya (Journal of Political Studies, 2012)
Ethnicity as an issue has been faced by all multi-ethnic societies. But it is a matter of great apprehensions and graver outcomes in those societies which are going through postconflict reconstruction, like Afghanistan is today. The paper will discuss in detail the ethnic groups, which exist in Afghan society along with the country’s ethnic history. This paper attempts to analyze the fact how social and political objectives of ethnic groups are liable to be accommodated in the new structure of Afghan State. It will also argue about the composition of ethnic groups, impact of war on ethnic communities, and why the ethnic fault lines may continue and under what circumstances, they may fade away?